Estudo comparativo entre bupivacaína 0,25% e 0,5% no bloqueio de plexo braquial via axilar guiado por ultrassom empregando cromatografia liquida acoplada à espectrometria de massas - Ferraro, Leonardo Henrique Cunha [UNIFESP] (2016)
Introduction: The risk of systemic toxicity when using bupivacaine is a persistent problem, making its pharmacokinetic study crucial to the safety of regional anesthesia (RA). A few evidences exist regarding the effect of different concentrations of this drug on peak plasma levels. The present study compares two bupivacaine concentrations to establish how the concentration and exchange area affect the peak plasma level of this drug during axillary brachial plexus block. Latency and postoperative analgesia periods were also compared. Methods: This prospective clinical study included 32 patients who were randomly assigned to two groups. In the 0.25% group, 10 ml of 0.25% bupivacaine was injected per nerve; in the 0.5% group, 5 ml of 0.5% bupivacaine was injected per nerve. Peripheral blood samples were collected every 15 min during the first hour and every 30 min during the second hour to establish serum level dosage. High performance liquid chromatography coupled with mass spectrometry (LC-MS) was used for sample analysis of bupivacaine in blood. Results: The groups reached peak plasma 45 min after axillary block, with no difference between groups at any evaluated time point. No patient reported pain before discharge from the recovery room. The 0.5% group showed briefer latencies compared with the 0.25% group (10.67 +/- 3.71 x 17.33 +/- 5.30 min, respectively). Conclusions: For axillary brachial plexus block, concentration and exchange area are equally important in determining peak plasma. However, concentration inversely affects the latency period.